Methodology for Simplifying 3D Geometric Descriptions for Web Visualization of the ATLAS Detector - Kekelia, Besik; Kekelia, Besik; Alikhanov, Aleksandre (International Scientific-practical Conference: „Modern Challenges and Achievements in Information and Communication Technologies“ Transactions, 2026)
3D modeling technologies play an important role in the modern world in scientific, engineering, and educational processes. In this research, a method for simplifying 3D geometric descriptions has been developed, which includes object optimization, reduction of polygon count, and more. The results showed that simplification of ATLAS detector models is possible by 94% in terms of objects and 98% in terms of polygons, while maintaining visual accuracy. This approach ensures the efficient use of models in virtual and web visualization applications.The significance of this research lies in the fact that maintaining high visualization quality and achieving optimization simultaneously is rarely possible. The presented methodology demonstrates how complex scientific data can be transformed into more accessible and efficient web applications.